Left atrioventricular coupling index measured by echocardiography in heart failure with preserved ejection fraction - Hai Nguyen Ngoc Dang; Thang Viet Luong; Hung Khanh Tran; Ny Ha Tuyet Le; Minh Hoang Nhat Nguyen; Thang Chi Doan; Hung Minh Nguyen (Scientific Reports)
Abstract Heart failure (HF) is a global health burden, with high hospitalization and mortality rates. Timely diagnosis is crucial in the management of HF. While noninvasive imaging techniques generally assess changes in the left atrium (LA) or left ventricle (LV) alone, the application of physiological connections between these chambers as echocardiographic parameters, such as the left atrioventricular coupling index (LACI), may be valuable as an early marker of HF. We conducted a cross-sectional study in which 1145 Vietnamese individuals were selected and 160 subjects met the inclusion criteria. These participants were divided into patient and healthy control groups, with 60 HF patients. LACI levels were significantly greater in HF patients, especially those with preserved ejection fraction (HFpEF), than in those with reduced ejection fraction (HFrEF) and controls (59.16 ± 17.94% vs. 41.28 ± 15.27% and 13.15 ± 3.92%, respectively). The LACI showed strong diagnostic value for HFpEF, with an area under the curve (AUC) of 0.951 and an optimal threshold of 33.07 (sensitivity: 97.1%, specificity: 87.3%). Multivariate analysis confirmed LACI as an independent predictor of HFpEF (OR = 1.144, 95% CI 1.087–1.205). Overall, LACI has emerged as an accessible, promising tool for diagnosing HFpEF.